2018
DOI: 10.11152/mu-1327
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the nail unit reveals quantitative and qualitative alterations in patients with psoriasis and psoriatic arthritis

Abstract: Our study shows that ultrasonography may be a potential advantage in clinical practice. Our results strengthen the information already available in the literature and add quantitative parameters for ultrasonography of the nail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
4
16
2
1
Order By: Relevance
“…Several authors have shown that NPT, NMT, and NBT were greater in psoriatic patients than controls [9,11,13,14,32,[34][35][36][37][38]. The present study only detected this increase in NPT.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Several authors have shown that NPT, NMT, and NBT were greater in psoriatic patients than controls [9,11,13,14,32,[34][35][36][37][38]. The present study only detected this increase in NPT.…”
Section: Discussioncontrasting
confidence: 67%
“…US examination can detect many changes to psoriatic nails, even in the absence of clinical findings [9][10][11][12][13]. Wortsman et al described and classified 4 types of US TS changes, ranging from the earliest to the most severe: focal hyperechoic involvement of the ventral plate without involvement of the dorsal plate (type I), loosening of the borders of the ventral plate (type II), appearance of wavy plates (type III), and loss of definition on both plates (type IV) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, magnetic resonance can also be used in some specific situations, especially when periungual soft tissues and bone involvement need to be further evaluated . In psoriasis, nail plate thickness can be useful in discriminating between patients with psoriatic nail involvement and healthy controls . Hypervascularity, viewed as an increase in Doppler signal, is related to increased disease activity .…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies on nail psoriasis are based on ultrasound and magnetic resonance evaluation . To our knowledge, there is no investigation of elastography.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in our study images gained from d1 and nd1 had insufficient quality, although repeated attempts to visualize these NU were performed. The difficulties were related to the limitations of our probe (inability to fit the (18)(19)(20). The pioneers of a nail plate thickness analysis using ultrasound transmission time were Finlay et al (21).…”
Section: Hf-usgmentioning
confidence: 99%